Cellular and clinicopathological features of the IL-33/ST2 axis in human esophageal squamous cell carcinomas - Guanglin Cui; Jingli Ren; Gang Xu; Zhenfeng Li; Wei Zheng; Aping Yuan (Cancer Cell International, 2018)
Abstract Background Emerging evidence has suggested that interleukin (IL)-33 and its primary functional receptor ST2 are involved in the pathogenesis of tumorigenesis. Methods Using immunohistochemistry (IHC) and double immunofluorescence staining, we characterized the cellular and clinicopathological features of the IL-33/ST2 axis in different compartments in human esophageal squamous cell carcinoma (ESCC) surgical specimens. Results IHC data revealed an increased expression of IL-33-immunoreactivity (IR) and ST2-IR located in both ESCC cells and tumor stromal cells; which were associated with advanced clinicopathological features such as TNM stages and node involvement. However, the Kaplan–Meier analysis showed that densities of neither IL-33 positive nor ST2 positive cells in both the ESCC mass and stroma were associated with the overall survival rate in patients with ESCC. Double immunofluorescence staining for cellular feature analysis demonstrated that these IL-33 positive and ST2 positive cells in ESCCs were with a high proliferation rate, and IL-33-IR was frequently co-expressed with ST2-IR in both ESCC and stromal cells. Conclusion Significant altered cellular features of the IL-33/ST2 axis in ESCCs were associated with advanced clinicopathological variables. The data suggest that the IL-33/ST2 axis might be involved in the progression of human ESCCs.